2011
DOI: 10.1103/physreva.84.023836
|View full text |Cite
|
Sign up to set email alerts
|

Coupled states of electromagnetic fields with magnetic-dipolar-mode vortices: Magnetic-dipolar-mode vortex polaritons

Abstract: Under the influence of the material environment, electromagnetic fields in the near-field regime exhibit quite different nature from those in the far-field free space. A coupled state of an electromagnetic field with an electric or magnetic dipole-carrying excitation is well known as a polariton. Such a state is the result of the mixing of a photon with an excitation of a material. The most discussed types of polaritons are phonon-polaritons, exciton-polaritons, and surface plasmon-polaritons. Recently, it was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(58 citation statements)
references
References 40 publications
1
57
0
Order By: Relevance
“…The properties of the MDM oscillations inside a ferrite disk are well observed numerically due to the ANSOFT HFSS program [19,20,23]. From the HFSS studies of microwave structures with thin-film ferrite disks, one has strong regularity of the results.…”
Section: Discussion On Credibility Of the Numerical Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…The properties of the MDM oscillations inside a ferrite disk are well observed numerically due to the ANSOFT HFSS program [19,20,23]. From the HFSS studies of microwave structures with thin-film ferrite disks, one has strong regularity of the results.…”
Section: Discussion On Credibility Of the Numerical Resultsmentioning
confidence: 89%
“…Following these results one observes restoration of an entire transmission spectrum when handedness of a sample is changed together with change of direction of a bias magnetic field. As it was shown in Refs [7,20,21], helicity of the near field is originated from double-helix resonances of MDM oscillations in a quasi-2D ferrite disk. For two helical modes, giving a double-helix resonance in a ferrite disk, there is no parity (  ) and time-reversal (  ) invariance -the  -invariance.…”
Section: Microwave Chirality Discriminationmentioning
confidence: 90%
See 2 more Smart Citations
“…There are small ferrite particles with magnetic-dipolar-mode (MDM) [or magnetostatic (MS)] oscillations [13]. In a series of recent publications, it was shown that small ferrite-disk particles may have unique spectral properties of MDM oscillations and the near fields originated from such particles are microwave superchiral fields with strong subwavelength localization of electromagnetic energy [14][15][16][17][18][19][20][21]. Specific long-distance topological properties of these fields are exhibited in the effects of path-dependent interference [22].…”
Section: Introductionmentioning
confidence: 99%